PROGRAM PENGUATAN LITERASI SEKOLAH DAN MASYARAKAT PADA MASA PANDEMI COVID - 19 DI DESA PANGAUBAN BANDUNG BARAT - Hosyatul Aliyah; Andini Putri Aryani; Nazri Nur Nawari (LPPM STAI Darul Falah, 2022)
People's reading interest is also affected by the current Covid-19 pandemic. West Java community reading index decreased from 68% to 61.49%, not least in Pangauban Batujajar, West Bandung. The program to strengthen school and community literacy aims to foster the spirit of reading and love of knowledge, improve literacy skills and optimize the literacy culture of the community. This community service partner is the manager of Taman Baca Masyarakat (TBM), government officials, students and the surrounding community. The method of community service is integrated with the activities of KKN STAI student Darul Falah, through book donation activities, literacy houses, reading lessons, virtual sharing, literacy workshops and volunteer educators. The results of the field findings obtained that children are very enthusiastic about the presence of literacy houses. Elementary and junior high school students can conduct book reviews, literacy workshop results, and local people of mobile phone users are more aware of health literacy after virtual sharing through whatsapp application. It can be concluded that community service through literacy strengthening programs helps increase reading interest and optimize people's literacy culture in the covid-19 pandemic.